Nitromethane conjugate addition to 2-[(1E,3E)-4-arylbuta-1,3-dien-1-yl]-4H-chromen-4-ones - Albuquerque, Hélio (2020)
Conjugate addition reaction of nitromethane to the extended π- conjugated system of several chromone derivatives afforded the 1,6-conjugate addition products, together with structure complex oxygen heterocycles through tandem processes.